ESBL/AmpC-Producing Escherichia coli in Wild Boar: Epidemiology and Risk Factors - Nicoletta Formenti; Stefania Calò; Giovanni Parisio; Flavia Guarneri; Laura Birbes; Alessandra Pitozzi; Federico Scali; Matteo Tonni; Federica Guadagno; Stefano Giovannini; Cristian Salogni; Adriana Ianieri; et al. (Animals, 2021)
The complex health problem of antimicrobial resistance (AMR) involves many host species, numerous bacteria and several routes of transmission. Extended-spectrum β-lactamase and AmpC (ESBL/AmpC)-producing Escherichia coli are among the most important strains. Moreover, wildlife hosts are of interest as they are likely antibiotics free and are assumed as environmental indicators of AMR contamination. Particularly, wild boar (Sus scrofa) deserves attention because of its increased population densities, with consequent health risks at the wildlife–domestic–human interface, and the limited data available on AMR. Here, 1504 wild boar fecal samples were microbiologically and molecularly analyzed to investigate ESBL/AmpC-producing E. coli and, through generalized linear models, the effects of host-related factors and of human population density on their spread. A prevalence of 15.96% of ESBL/AmpC-producing E. coli, supported by blaCTX-M (12.3%), blaTEM (6.98%), blaCMY (0.86%) and blaSHV (0.47%) gene detection, emerged. Young animals were more colonized by ESBL/AmpC strains than older subjects, as observed in domestic animals. Increased human population density leads to increased blaTEM prevalence in wild boar, suggesting that spatial overlap may favor this transmission. Our results show a high level of AMR contamination in the study area that should be further investigated. However, a role of wild boar as a maintenance host of AMR strains emerged.